2018
DOI: 10.5415/apallergy.2018.8.e39
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skin prick test to screen dust mite sensitization in chronic respiratory diseases in Southern Vietnam

Abstract: BackgroundIn the view of the epidemic growth of sensitization to indoor allergens in Southern Vietnam, there is a requirement to screen large population.ObjectiveTo evaluate skin prick tests (SPTs) as predictors of positive specific IgE (sIgE) to dust allergens, among patients with chronic respiratory diseases (CRDs).MethodsThe sensitization to Blomia tropicalis (Blo t), Dermatophagoides pteronissinus (Der p), and Blattella germanica allergens (Bla g) were evaluated among 610 CRD, both SPT (≥4 mm) and sIgE by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The present study showed the high prevalence of sensitization against Df, followed by Dp, Bt, storage mites and cockroach. Among patients with chronic respiratory diseases in southern Vietnam, Df, Bt, Dp and cockroach droppings were the most frequent sensitizers ( 17 , 19 ). Another study from northern Vietnam showed the high prevalence of sensitization to Bt, Dp, Df, and cockroach, while in the Central Highlands region, Dp was the predominant allergen, followed by Df, Bt, and cockroach ( 7 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed the high prevalence of sensitization against Df, followed by Dp, Bt, storage mites and cockroach. Among patients with chronic respiratory diseases in southern Vietnam, Df, Bt, Dp and cockroach droppings were the most frequent sensitizers ( 17 , 19 ). Another study from northern Vietnam showed the high prevalence of sensitization to Bt, Dp, Df, and cockroach, while in the Central Highlands region, Dp was the predominant allergen, followed by Df, Bt, and cockroach ( 7 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…House dust mites are the most common allergen in: China, Thailand, Singapore and Vietnam [7]. Mites cause cross-reactions with shrimps, which are a very common food in the Far East [7].…”
Section: Discussionmentioning
confidence: 99%
“…House dust mites are the most common allergen in: China, Thailand, Singapore and Vietnam [7]. Mites cause cross-reactions with shrimps, which are a very common food in the Far East [7]. Cross allergies also occur between an allergy to tree pollen (birch, hazel) and raw vegetables and fruits [8].…”
Section: Discussionmentioning
confidence: 99%
“…This issue also contains a report on the sensitization of Blomia tropicalis , Dermatophagoides pteronissinus , and Blattella germanica allergens evaluated by skin prick test and allergen-specific IgE in chronic respiratory diseases from Southern Vietnam [ 14 ], and a case report of anaphylactic shock induced by tipepidine hibenzate (Asverin), an antitussive drug, in 1 year old child [ 15 ].…”
mentioning
confidence: 99%